The social and political thought of R.G. Collingwood - Boucher, David 1951- (Cambridge University Press, 1989)
This is the first comprehensive study of the political philosophy of the British philosopher R. G. Collingwood, best known for his contributions to aesthetics and the philosophy of history. However his political thought, and in particular his book The New Leviathan, have been neglected, even dismissed in some quarters. Professor Boucher argues for the importance of this political theory and provides a perspicuous account of its development and originality. He contends that The New Leviathan is an attempt to reconcile philosophy and history, theory and practice. Collingwood's distinctive contribution to modern political and social thought is seen as his sustained project of distinguishing utility from right, and right from duty; the passion for history coincides with the ethical thought because Collingwood wishes to identify dutiful, or moral, action with a historical civilization. Drawing on a wealth of manuscript material, this book will prove invaluable to political philosophers and intellectual historians
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Collingwood, R. G. / (Robin George) / 1889-1943; Collingwood, Robin G. -- 1889-1943; Soziologie; Politische Philosophie; Politisches Denken; Politische Wissenschaft